2019
DOI: 10.26502/fccm.92920063
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Lipid and Hematological Profile among Blood Donors in European Gaza Hospital, Palestine

Abstract: Background: There is an important shortage of blood in the greatest blood banks worldwide to meet up with requirements for numerous medical interventions. Limited studies have associated regular blood donation to the lowering of lipid function parameters. Assessing the lipid function is a classical method of evaluating an individual's risk for coronary heart disease. Objective:The general goal of the study is to determine lipid and hematological profile among blood donors in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…In addition, BMI and WHR were found to be similar between the regular and first-time blood donors. While our report on BMI value agrees with two researchers in Iran and Palestine, 6,18 other groups claimed that BMI was lower 20 and higher 21 in regular blood donors when compared to the first-time donors. The latter is due to the high interest of obese people who understood the health benefits of blood donation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, BMI and WHR were found to be similar between the regular and first-time blood donors. While our report on BMI value agrees with two researchers in Iran and Palestine, 6,18 other groups claimed that BMI was lower 20 and higher 21 in regular blood donors when compared to the first-time donors. The latter is due to the high interest of obese people who understood the health benefits of blood donation.…”
Section: Discussionsupporting
confidence: 92%
“…This indicated that sociodemographic characteristics did not affect the results as a confiding, which is in congruence with previous reports. 6,18 However, the number of male donors was found to be higher in regular blood donors (RBD) and first-time blood donors (FTD), compared to females, albeit statistically insignificant. Rizvi's report showed a similar trend.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation